Komunikasi M2M Kognitif Berbasis PRMA dengan Multi Ultra Frame dan Payload Exchange - Eko Arifianto; Aghus Sofwan; Teguh Prakoso (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2019)
M2M communication is the process of exchanging data between devices on a network of capillary systems. The communication channel used is an empty space on a TV channel with a cognitive radio mechanism combined PRMA with a fixed and periodic scheme. The scheme has a working system that allows PRMA to place data in the same free space, which causes collisions. Therefore, it needs repetition, which requires more energy and causes inefficient communication. Thus, a Multi Ultra Frame (MUF) and Payload Exchange (PE) data exchange scheme is proposed to reduce collisions and repetition by giving grades and features to the data, with the aim to achieve optimal use of empty space. An indication of efficient communication is the optimal use of empty space, which affects the throughput (PT), duty cycle (Cyl), and interference ratio (fo). The higher PT and the lower Cyl and fo, the more efficient the communication. MUF and PE schemes produce PT of 99-41%, Cyl of 1-4.4%, and fo of 10-33%. Fixed and periodic schemes produce PTof 81-21%, Cyl of 2-9%, andfo of 15-52%. Optimization of MUF and PE schemes producePTof 99-70%, Cyl of 0.5-2.2%, and fo of 8-14%. Optimization of fixed and periodic schemes produce PTof 66-35%, Cyl of 3-6%, and fo of 19-28%.